Comparison of HRCT Chest Findings of COVID-19 Patients Having Clinical Co-morbid to Those Without Co-morbid Disease - Qayyum, Adil; Adil, Ruqqayia; Balooch, Salahuddin; Khan, Sara; Amin, Zafar; Mahmood, Rashid (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the severity of High-Resolution Computed Tomography Chest findings of COVID-19 patients having co-morbid in comparison to those without co-morbid. Study Design: Comparative cross sectional study.Place and Duration of the Study: Radiology Department Combined Military Hospital, Multan Pakistan, from Mar to Sep 2020.Methodology: Data was collected through the medical record system of positive COVID-19 tests. Patients were divided into patients with no co-morbidities and others having co-morbidities. Two radiologists interpreted High-Resolution Computed Tomography chests independently to assess the disease severity in these two Groups. Co-morbidities included diabetes mellitus, hypertension, chronic renal disease, heart disease, Chronic Obstructive Pulmonary Disease and liver diseases.Results: A total of 200 patients were included. Out of 121 male patients, 85 had co-morbidities (71 had moderate to severe lung involvement; 14 had mild lung involvement); while 36 had no co-morbidities (5 had moderate to severe lung involvement; 31 had mild lung involvement). Out of 79 female patients, 47 had co-morbidities (15 had moderate to severe lung involvement; 32 had mild lung involvement); while 32 had no co-morbidities (3 had moderate to severe lung involvement; 29 had mild lung involvement).Conclusion: The severity of lung involvement was remarkably higher in patients with associated co-morbidities compared to no co-morbidities. Older age male patients having co-morbidities pose a risk factor for the severity of disease progression as compared to younger age female patients having no co-morbidities